2019
DOI: 10.1128/mra.01486-18
|View full text |Cite
|
Sign up to set email alerts
|

Complete Genome Sequence of Pantoea agglomerans TH81, Isolated from a Permafrost Thaw Gradient

Abstract: In this report, we describe the complete genome assembly of a Pantoea agglomerans isolate, TH81, collected from a boreal forest soil associated with permafrost thaw. Using both Nanopore and Illumina sequences, we assembled four circular contigs totaling 4,983,504 bp (N50, 4,127,869 bp), a complete chromosome with three plasmids.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“… van der Voort et al (2016) and Yang et al (2020) have also showed that soils stressed by drought and heat disturbance, respectively, were found to have overrepresented populations of known plant pathogens including members of Comamonadaceae and Erwiniaceae. Although few studies have looked at the effects of physical disturbances on microbiomes specifically in arctic or subarctic soils, in previous research we cultured and isolated bacterial strains belonging to Erwiniaceae from the FPES MD soil plot ( Humphrey et al, 2019 ). It is possible that the higher presence of bacterial groups including known plant-pathogenic bacteria found in the MD soil microbiomes is leading to the decrease in associated plant growth, caused by a disruption in nutrient cycling and direct alterations to the plant rhizospheres.…”
Section: Discussionmentioning
confidence: 99%
“… van der Voort et al (2016) and Yang et al (2020) have also showed that soils stressed by drought and heat disturbance, respectively, were found to have overrepresented populations of known plant pathogens including members of Comamonadaceae and Erwiniaceae. Although few studies have looked at the effects of physical disturbances on microbiomes specifically in arctic or subarctic soils, in previous research we cultured and isolated bacterial strains belonging to Erwiniaceae from the FPES MD soil plot ( Humphrey et al, 2019 ). It is possible that the higher presence of bacterial groups including known plant-pathogenic bacteria found in the MD soil microbiomes is leading to the decrease in associated plant growth, caused by a disruption in nutrient cycling and direct alterations to the plant rhizospheres.…”
Section: Discussionmentioning
confidence: 99%
“…The unicycler_polish tool of Unicycler version 0.4.8 [ 32 ] was used to polish the flye assemblies with the Illumina reads as input. For isolates TH26, TH81 and TH88, ONT long-read assemblies that were previously published in Haan et al 2019 and Humphrey et al 2019 respectively were used as inputs for unicycler_polish [ 33 , 34 ].…”
Section: Methodsmentioning
confidence: 99%
“…The unicycler_polish tool of Unicycler v0.4.8 (Wick et al 2017) was used for genome polishing with the Illumina reads and the Flye assembly as inputs. For isolates TH26 and TH81, ONT long-read assemblies previously published in Haan et al 2019 and Humphrey et al 2019 respectively were used as inputs for unicycler_polish. These assemblies were annotated with RAST tool kit (RASTtk) in PATRIC v3.6.3 using the Genome Annotation Service (Brettin et al 2015).…”
Section: Methodsmentioning
confidence: 99%